Generation and regeneration of scalable fonts - Zhou, Hao (2009)
In this thesis, two important problems in the font technology are studied: outlined font generation from its bit-mapped image and font rasterizing from its outlined representation to its bit-mapped representation. New algorithms are developed. Fonts are collections of letters and letter shaped symbols which are used in word processor and publishing systems. The objective of font generation is tightness and efficiency. It means that the curved representation generated should lie near the data points of the font's contours, and that as few curve pieces as possible are used. The objective of font rasterizing is high speed, efficient use of memory and good robustness. A new font, generation algorithm is presented to generate piecewise Bezier curve representation of fonts from their bit-mapped images.